Request Batching Self-Configuration in Byzantine Fault-Tolerant Replication - Sá, Alírio Santos de; Freitas, Allan Edgard Silva; Macêdo, Raimundo José de Araújo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Replication techniques that tolerate byzantine failures have been applied in distributed computing to cope with hostile environments in which system components may fail due to malicious or natural causes (e.g., intrusions). From the seminal work of Lamport, Pease and Shostak on Byzantine Generals, in 1982, Castro and Liskov proposed in 1999 a successful solution, named PBFT, which overcomes performance drawbacks of previous ones, based on a number of protocol optimizations, including the use of request batching. Such a work motivated several other works as extension of the PBFT protocol, improving PBFT performance in certain computing environment conditions. In these solutions, which we call PBFT-family protocols, the tuning of the request batching parameters are realized in design time. However, such configuration may not yield the desired performance in dynamic distributed systems where the underlying characteristics change dynamically (e.g., workload, channel QoS, network topology, etc.). To answer to this challenge, this paper proposes an innovative solution to the dynamic configuration of batching parameters inspired on feedback control theory. In order to evaluate its efficiency, the proposed solution is simulated in various scenarios and compared with the original version used in the PBFT-family protocols.